FRI0311 PREVALENCE AND CLINICAL MANIFESTATIONS OF ERASMUS SYNDROME IN SYSTEMIC SCLEROSIS: A CROSS-SECTIONAL STUDY. (June 2019) - Azevedo, Soraia; Neves, Joana; Faria, Daniela; Silva, Joana; Rodrigues, Joana; Peixoto, Daniela; Tavares-Costa, José; Alcino, Sérgio; Afonso, Carmo; Teixeira, Filipa
Abstract : Background: Erasmus syndrome (ErS) is defined by the association of exposure to silica with the subsequent development of systemic sclerosis (SSc), with or without associated silicosis. Objectives: The objectives of this study were, on one hand, to evaluate the prevalence of ErS in a population of SSc patients and to characterize the cases and, on the other hand, to evaluate the clinical and laboratory characteristics of SSc patients with or without exposure to silica. Methods: We performed a cross-sectional study of the patients with SSc in our department. Demographics, clinical and laboratory data were collected from all patients with SSc diagnosed according to ACR/EULAR criteria. Moreover, a telephone call was made in order to detail the professional activity and possible exposure to silica. Results: The prevalence of ErS in this population was 15.3% (9/59). All cases identified were male, corresponding to 75% of men with SSc followed at our department. There was a statistically significant association between ErS and male gender (p<0.001), initial pulmonary manifestation (p=0.025), history of digital ulcers (p=0.014) and smoking (p=0.047). On the other hand, a lower risk of gastrointestinal involvement was found in ErS cases (p=0.008). All patients with ErS had positive autoantibodies (mainly anti-Scl70 and anti-centromere) with titters tending to be higher than SSc without ErS, although without statistically significant differences. In addition, although with no statistical significance, we found that pulmonary artery systolic pressure (PASP) estimated by echocardiogram was higher in patients with ErS. Conclusion: In our study, prevalence of ErS was higher than data from previously published literature. For a more accurate ErS diagnosis it is necessary to be aware of and investigate less intense silica exposures, which may have occurred many years before diagnosis. Statistically significant differences were found between ErS and SSc without exposure to silica; this fact may have impact in diagnosis, treatment and prognosis. References: [1] Erasmus L.D. et al. [2] Pollard K. M. et al. [3] West S. G.et al. [4] Elhai M et al. [5] Ferri C etal [6] Mora G. F. et al. [7] Haustein UH et al. [8] Rosenman KD et al. [9] Van Loveren H et al. [10] Rocha L.F. et al. [11] Sharma RK et al. [12] Rustin M. H. et al. [13] Marie I et al. [14] Magnant J et al. [15] Van den Hoogen F et al. [16] Sebastiani M et al. [17] Leroy EC et al. [18] Marie I, et al. [19] Elhai M et al. [20] Makol A. et al. [21] Rodnan G.P. et al. [22] Subrata Chakrabarti et al. [23] Bello S et al. [24] Burns C.J. et al. [25] Galluccio F et al. [26] Forbes A et al. [27] MacHugh NJ et al. [28] Czirjak L et al. Disclosure of Interests: None declared